Pengaruh Usia, Pengalaman Kerja, Tingkat Pendidikan, dan Kompleksitas Tugas terhadap Efektivitas Pengguna Sistem Informasi Akuntansi - Anjani, Putu Widya; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2018)
Every company needs a good management in running its business to achieve its goals well. Management needs accurate information from accounting information systems. The purpose of this study was to determine the influence of age, work experience, education level, and task complexity to the effectiveness ofthe accounting information system user. The sample used to be 69 respondents with purposive sampling method. Data was collected through questionnaires and interviews. The data analysis technique is used multiple linear regression analysis. The result of the analysis shows that age and task complexity have the negative effect, while the work experience and education level have a positive effect on the effectiveness of users of accounting information system. To improve the effectiveness of users of accounting information systems it is important to pay attention to employee ability factors and conduct training for employees so that the knowledge of the employees is evenly distributed. Keywords : Age, work experience, education level, and task complexity.